Taxonomy of the genus Diochus Erichson, 1839 (Coleoptera: Staphylinidae, Staphylininae, Diochini) in China with descriptions of four new species - Zhou, Yu-Lingzi; Zhou, Hong-Zhang (Zootaxa, 2016)
This paper studies the taxonomy of the genus Diochus Erichson, 1839 (Coleoptera: Staphylinidae, Staphylininae, Diochini) from China. Four new species are described: Diochus bicornutus sp. nov. from Fujian, Hainan, Zhejiang, Guangxi and Yunnan, D. ampullaceus sp. nov. from Guangxi, D. bisegmentatus sp. nov. from Hainan and Yunnan, and D. membranaceus sp. nov. from Fujian. All other species previously reported from China are redescribed based on the examination of the holotypes, except the holotype of D. antennatus (Motschulsky, 1858), which was missing. Line drawings of the now missing holotype of D. antennatus (Motschulsky, 1858) are provided. A lectotype is designated for D. conicollis (Motschulsky, 1858). The Chinese fauna of the genus Diochus is now represented by eight species (four doubtfully recorded) and a key to all the Chinese species is provided. The type specimens of the new species are deposited in the Institute of Zoology, Chinese Academy of Sciences (IZ-CAS).